Changes in the composition of the upper respiratory tract microbial community in granulomatosis with polyangiitis. (February 2019) - Lamprecht, Peter; Fischer, Nicole; Huang, Jiabin; Burkhardt, Lia; Lütgehetmann, Marc; Arndt, Fabian; Rolfs, Ida; Kerstein, Anja; Iking-Konert, Christof; Laudien, Martin
Abstract: Dysbiosis¸ i.e. changes in microbial composition at a mucosal interface, is implicated in the pathogenesis of many chronic inflammatory and autoimmune diseases. To assess the composition of the microbial upper respiratory tract (URT) community in patients with granulomatosis with polyangiitis (GPA), we used culture-independent high-throughput methods. In this prospective clinical study, nasal swabs were collected from patients with GPA, patients with rheumatoid arthritis (RA, disease control), and healthy controls. Nasal bacterial taxa were assessed using V3–V4 region 16S rRNA amplicon sequencing. Staphylococcus aureus, Haemophilus influenza, and entero- and rhinoviruses were detected using qPCR. Unbiased metagenomic RNA sequencing (UMERS) was performed in a subset of samples to determine the relative abundance of bacterial, fungal, and viral species. A trend toward reduced microbiome diversity was detected in GPA samples compared with healthy controls. The abundance of bacterial taxa and microbial richness were significantly decreased in GPA samples compared with RA samples. The relative abundance of bacterial families shifted, with increased Planococcaceae and decreased Moraxellaceae, Tissierellaceae, Staphylococcaceae, and Propionibacteriaceae in GPA and RA. Further, decreased abundance of Corynebacteriaceae, and Aerococcaceae was observed in GPA samples. Significantly more colonization of S. aureus was seen in the nasal microbiome of GPA compared with RA and healthy control samples. H. influenzae colonization was also observed in GPA samples. UMERS detected the presence of rhinoviral sequences in some GPA samples. Thus, our study uncovered changes in the URT microbial composition in patients with GPA and RA, suggesting that both immunosuppression and disease background affect the URT microbiome. Complex alterations of host-microbiome interactions in the URT could influence chronic endonasal inflammation in GPA. Highlights: High-throughput sequencing allows culture-independent analysis of the microbiome. The nasal microbial composition is changed in granulomatosis with polyangiitis. Both immunosuppression and disease background affect the nasal microbiome.